Evaluación funcional de los software de suspensión, reactivación y apagado para los cpus del laboratorio de la carrera informática, Espam MFL. - Ganchozo Intriago, Ángel Humberto (2015)
This research that the authors have done is to assess a number of functional software with features for controlling CPUs likewise analyzing economic and accounting aspects life, minimizing costs and extending the utility of the same, Throughout the pages of this work, the reader will understand details of the investigation and the reasons for it and the results graphically and textually shape documentation which have been evaluated in a first investigation the Radmin software, Vnc Teamviewer and these results gave way to the selection of software A and B would be for evaluation by choosing the comparison study and Teamviewer Radmin software; comparative study tests were conducted in the laboratory building 102 career informatics ESPAM MFL using evaluative tool as a checklist of which results were quantified to show graphically the results and defend the ideas facts.